How Homogenous are the Madhesis? Implications for Inclusive and Affirmative Agendas - Subedi, Madhusudan; Gautam, Tika Ram (Journal of Development and Administrative Studies, 2018)
Ethnicity, social inclusion/exclusion and inequality have been much more important and also equally debatable issues in contemporary Nepal. Some scholars (Bhattachan, 2009, 1995; Gurung, 1997; Gurung, 2012; Lawoti, 2005, 2012; Mabuhang, 2012) argue Bahuns, particularly hill Bahuns is the most privileged group with highest access to resources and opportunities and all other non-Brahmans such as Janajatis, Dalits, Madheshi, Muslims, and so on are the most deprived/excluded groups with least access to resources and opportunities. This paper, in contrast, based on NSII(2014) data, argues that Madhesis is neither a single nor a homogeneous group rather it is a broader caste/ethnic category which includes a number of Tarai/Madhesh caste/ethnic groups distinctly different from each other in terms of education, health, economy and politics. Some caste/ethnic groups, within Tarai/Madhesh groups or Madhesis, have better access to resources and opportunities and other Tarai/Madhesh groups have poor access to resources and opportunities. This kind of intra-group inequality can also be observed within all caste/ethnic groups of Tarai/Madhesh; Tarai Brahman/Chhetri, Tarai Dalit, Tarai Janajati, other Tarai Castes, and Muslims including heterogeneous Bahuns (Gautam, 2015). Therefore, Madhesis, as broader Tarai/Madhesh caste/ethnic group, is neither a single nor a homogeneous group rather it is a heterogeneous category with wider inter-group inequality in terms of access to resources and opportunities. The Journal of Development and Administrative Studies (JODAS), Vol. 24 (1-2), pp. 25-38